Novel heteroatom sulfur porphyrin organic polymer as a metal-free electrocatalyst for acidic oxygen reduction reaction. (1st May 2021) - Yan, Wei; Cao, Shoufu; Xiao, Zuoxu; Dai, Fangna; Xing, Tao; Li, Zhi; Chen, Yanli; Lu, Xiaoqing; Li, Xiyou
Highlights: S-POP is firstly developed as a metal-free catalyst for acidic ORR. The best result achieves among metal-free polymer-based ORR catalysts. Introduction of S atoms stimulates ORR activity of aza N species in S-POP. aza N species in S-POP promotes *O desorb process and decreasing the overpotential. Abstract: The rational design of a highly reactive electronic structure as the active sites is crucial for the development of oxygen reduction reaction (ORR) catalysts. Herein, a unique ethynyl-linked sulfur-containing porphyrin organic polymer (S-POP) is firstly developed as a metal-free catalyst for ORR under acidic conditions, which possess intrinsic porous structures and easily accessible active sites for the adsorption of oxygen. The S-POP exhibits a superior ORR performance with onset potential of 0.82 V and half-wave potential of 0.72 V, achieving one of the best results among metal-free polymer-based ORR catalysts in acidic conditions, the high ORR activity of S-POP is attributed to the exposure of active sites under the test environment. In particular, it is discovered that after replacing pyrrole N by S atoms, the remaining aza N in S-POP exhibit higher ORR activity than those in conventional porphyrin organic polymer (POP). Density functional theory calculations shows that the significant improvement of S-POP over POP is from the redistribution and reduction of the density of charges on aza N, which promotes *O desorb process and decreases the overpotential. This work provides a novel guidance towards designing and modifying metal-free ORR electrocatalysts with a clear electronic structure as the active sites. Graphical abstract: A unique ethynyl-linked S -containing porphyrin organic polymer is firstly developed as a metal-free catalyst for acidic ORR, achieving one of the best results among metal-free polymer-based ORR catalysts in acidic conditions. Image, graphical abstract